Murder License for Murder in the March; Reiterated in 2013 Approved Islamic Penal Code Regarding Mahdur al- Damm (Deserving Death) - Mohaddeseh Sadeghian Lemraski; Kalantari Kalantari; Iraj Goldoozian (AHKAM : Jurnal Ilmu Syariah, 2019)
In the case law of Iran, the punishment for a deliberate murder following the religion of Islam is retribution of the soul (qisas), but in cases, several retaliation orders have been eliminated, of such cases is Murder in the March and it is where a husband observes his wife and a barbarian man committing adultery and then commits the crime of murdering them. About the importance of this discussion, it is worth noting that the Article 302 of Islamic Punishment Code of 2013, also complying with the comment of the noted jurisprudents of Imamiyah, who have considered the murder of the wife and the barbarian adulterer by the husband the exclusion of retribution. Despite all criticisms made in the new Islamic Penal Code, it has again been reiterated and being slightly changed in the surface of the articles, they are still binding in accordance with the Article 630 of Islamic Punishment Code of sanctions sector, for this reason, efforts have been made in this research to study and lay out the aforementioned articles and present the previously conducted studies in this regard, dealing with these legal articles and the possibility to change them in order to resolve this problem. From the perspective of the case law, the Clause "E", the Article 302 of Islamic Penal Code, it can be misused by professional killers and be set forth as the Murder in the March. Although, the legislator has put punishment for Ta'zir or "deterrent" in the new law for arbitrary action without permission from the court and also taking measure based on the wrong belief but since in many cases, the perpetrators of honor murders, according to this decree, consider themselves right to commit this murder. It seems that the universality of the above decree has to be reduced and the punishment level for the arbitrary actions in such cases has to be added. The current research studies the well-known comment of the jurisprudents and its critique regarding Murder in the March related Murder License; reiterated in the Islamic Punishment Code approved in 2013 concerning Mahdor al-Adam.